2016
DOI: 10.1074/jbc.m116.747824
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Intein Inhibition by Platinum Compounds as an Antimicrobial Strategy

Abstract: Inteins, self-splicing protein elements, interrupt genes and proteins in many microbes, including the human pathogen Mycobacterium tuberculosis. Using conserved catalytic nucleophiles at their N-and C-terminal splice junctions, inteins are able to excise out of precursor polypeptides. The splicing of the intein in the mycobacterial recombinase RecA is specifically inhibited by the widely used cancer therapeutic cisplatin, cis-[Pt(NH 3 ) 2 Cl 2 ], and this compound inhibits mycobacterial growth. Mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 43 publications
1
62
1
Order By: Relevance
“…Expression of the ΔΔI-TM intein mutant indicated that splicing, N-terminal cleavage and C-terminal cleavage were arrested (Supporting Information Figure S2), yet no evidence of metal binding could be detected despite the presence of the putative metal binding residues. Platinum binding has been shown to be mediated mainly by the sidechains of Cys1 and Cys + 1 of the RecA intein (Chan et al, 2016;Zhang, Zheng, Callahan, Belfort, & Liu, 2011), suggesting, among other possibilities, that one or both Cys may be perturbed spatially or otherwise modified. Interestingly, the ΔΔI-TM (T70A/ N139A) mutant exhibited the most intense signal at exactly 18 Da less than the expected mass when measured by ESI-MS (monoisotopic M obs = 16,454.60 Da; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the ΔΔI-TM intein mutant indicated that splicing, N-terminal cleavage and C-terminal cleavage were arrested (Supporting Information Figure S2), yet no evidence of metal binding could be detected despite the presence of the putative metal binding residues. Platinum binding has been shown to be mediated mainly by the sidechains of Cys1 and Cys + 1 of the RecA intein (Chan et al, 2016;Zhang, Zheng, Callahan, Belfort, & Liu, 2011), suggesting, among other possibilities, that one or both Cys may be perturbed spatially or otherwise modified. Interestingly, the ΔΔI-TM (T70A/ N139A) mutant exhibited the most intense signal at exactly 18 Da less than the expected mass when measured by ESI-MS (monoisotopic M obs = 16,454.60 Da; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…the sidechains of Cys1 and Cys + 1 of the RecA intein(Chan et al, 2016;Zhang, Zheng, Callahan, Belfort, & Liu, 2011), suggesting, among other possibilities, that one or both Cys may be perturbed spatially or otherwise modified. Interestingly, the ΔΔI-TM (T70A/ N139A) mutant exhibited the most intense signal at exactly 18 Da less than the expected mass when measured by ESI-MS (monoisotopic M obs = 16,454.60 Da;Figure 2).…”
mentioning
confidence: 99%
“…Metal binding has been reported for other inteins, and often engages catalytic residues, which would stall protein splicing (47,(51)(52)(53)(54)(55)(56). Therefore, we chose to follow up on the observed copper and zinc inhibition by running in vitro MIG Prp8 A-1V assays to further assess effects on protein splicing over time (Fig.…”
Section: Splicing Inhibition Is Mechanistically Distinct Under Coppermentioning
confidence: 99%
“…Around a dozen intein structures have been solved so far, comprising mainly bacterial and archaeal inteins (63). These have proven useful for studying inteins as novel drug targets (51). As inteins often invade essential proteins in pathogens, inhibiting them from splicing out is an attractive option for developing new antimicrobials (51,64,65).…”
Section: Structural Insights Into the Prp8 Inteinmentioning
confidence: 99%
See 1 more Smart Citation